ANALYSIS OF BBM, LEC, AND SERK EXPRESSIONS IN CALLUS OF SUGARCANE (Saccharum officinarum L.) AT SOMATIC EMBRYOGENESIS DEVELOPMENT STAGES - Dewanti, Parawita (BRIN - Badan Riset dan Inovasi Nasional, 2022)
Callus formed in somatic embryogenesis is divided into two types, embryogenic and non-embryogenic callus. Embryogenic callus can be distinguished by the expression of genes as markers related to somatic embryogenesis which are expected to be used as markers to detect callus that has embryogenic capabilities in sugarcane. The aim of this study was to determine the expressions of somatic embryogenesis-related genes in sugarcane. The genes analysis was carried out using somatic embryogenesis callus and using a kit for RNA analysis. Results showed that there were expressions of Baby Boom (BBM), Leafy Cotyledon (LEC), dan Somatic Embryogenesis Receptor Like-Kinase (SERK) gene with specific primer of those three genes, which were collected from embryogenic callus in mass, globular, scutelar, and coleoptilar pre-embryo stages, meanwhile there were no expressions of those genes collected from non-embryogenic callus. Amplification result from PCR product of cDNA using three gene primers detected were in 500 bp for BBM, 400 bp for LEC, and 700 bp for SERK gene.